1994
DOI: 10.1128/mcb.14.11.7211
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of period mRNA cycling in Drosophila head and body tissues indicates that body oscillators behave differently from head oscillators.

Abstract: The period (per) gene is thought to be part of the Drosophila circadian pacemaker. The circadian fluctuations in per RNA and protein that constitute theper feedback loop appear to be required for pacemaker function, and have been measured in head neuronal tissues that are necessary for locomotor activity and eclosion rhythms. The per gene is also expressed in a number of neuronal and nonneuronal body tissues for which no known circadian phenomena have been described. To determine whether per might affect some… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
87
2

Year Published

1995
1995
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(97 citation statements)
references
References 34 publications
8
87
2
Order By: Relevance
“…All three Spalax Per genes are expressed in a wide variety of nonneural tissues as previously shown in Drosophila (53,54) and mice (39,41). In three of these tissues (liver, eye, and harderian gland) we found that the RNA levels for the three sPer genes oscillate.…”
Section: Discussion Adaptive Selection On Per Genes In Spalax To Lifementioning
confidence: 60%
“…All three Spalax Per genes are expressed in a wide variety of nonneural tissues as previously shown in Drosophila (53,54) and mice (39,41). In three of these tissues (liver, eye, and harderian gland) we found that the RNA levels for the three sPer genes oscillate.…”
Section: Discussion Adaptive Selection On Per Genes In Spalax To Lifementioning
confidence: 60%
“…6D). Studies in a variety of species have reported that each single cell contains a cellautonomous and self-sustained oscillator whose phases are not synchronized to each other in the absence of external time cues (34)(35)(36)(37)(38)(39). zCRY1a and zPER2 interact with each other, forming a heterodimer that functions as a repressor of CLOCK:BMALmediated transcription (40,41).…”
Section: Discussionmentioning
confidence: 99%
“…Per, a key pacemaker component (reviewed in ref. 31), has been shown to be expressed in both male and female gonads; however, male abdomens show a circadian oscillation of transcript levels that is absent in female abdomens (32). DGqC is an ideal transducer in this putative clock-input pathway, as it has the divergent Rh-binding exon and the nonvisual PLC-binding exon.…”
Section: Methodsmentioning
confidence: 99%